Design of Tools for Loading and Unloading Wheelchairs into/from Avanza Hatchback Cars Using an Ergonomics Approach - Yudiantyo, Wawan; Wirawan, Christina; Bierhoff, Yehezkiel (Universitas Kristen Maranatha, 2025)
Wheelchairs are necessary mobility aids for people with lower-limb disabilities. However, transporting a heavy electric wheelchair in a car presents challenges and can result in injuries to caregivers who assist with loading and unloading. The goal of this study was to create an ergonomic transfer assist that would make it easier and safer to transport wheelchairs into cars. The Avanza Hatchback and electric wheelchair were measured for width, length, base height, and weight. Using this information, a transfer assist with a slanted base was built using ergonomic principles to alleviate physical strain during loading and unloading. The design was also based on the REBA (Rapid Entire Body Assessment) score to determine the optimal posture. This study makes a unique addition because it focuses on specific aids for safe wheelchair transfers into and out of automobiles, where there is currently insufficient research.